HUBUNGAN TINGKAT KONSENTRASI DENGAN KETERAMPILAN BERMAIN FUTSAL TIM FUTSAL SMA IT FADHILAH PEKANBARU - Saputra, Wiky Ilham; Juita, Ardiah; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of this research is to determine the relationship between concentration level and futsal playing skills of the SMA IT Fadhilah Pekanbaru futsal team. Meanwhile, the benefits of this research are as a source of information, knowledge, reference for future research and as reading material for coaches and athletes in overcoming anxiety or mental toughness, especially in karate and other sports. Every research certainly has aims and objectives, based on the existing problem formulation, the aim to be achieved in this research is to find out the relationship between concentration levels and futsal playing skills. The results of data analysis carried out using the Pearson product moment correlation test show a positive relationship with a significant value of 0.028 and a calculated r of 0.629. So that 0.629 is found in the pearson correlation value degree guideline between 0.61 to 0.80, thus it can be interpreted that the relationship between concentration level and futsal playing skills has a strong correlation.Key Words: relationship between concentration, skill, futsal.